Perbandingan Penggunaan Media Sosial dalam Pengaruhnya terhadap Perilaku Pemilih di Indonesia dan Filipina - Juliansyah Akbar, Muhammad; Firmansyah, Rafi Ahmad Firmansyah; Muamalah, Riadhotul Muamalah; Hakim, Moh. Fathoni Hakim (Jurnal PUBLIQUE, 2026)
This study compares the influence of social media on voter behavior in Indonesia and the Philippines by examining the dominance of TikTok in Indonesia and Facebook in the Philippines. Using a comparative qualitative approach and David Easton’s Political System framework, the research analyzes how these platforms function as political inputs processed through algorithms and influencer networks, shaping voter perceptions and electoral choices. Findings show that TikTok is highly influential among Indonesian first-time voters due to its visual, emotional, and viral content that creates a homogenized information environment through the For You Page algorithm. In contrast, Facebook in the Philippines operates as a structured political arena supported by organized influencer networks and coordinated disinformation, significantly contributing to narrative formation and electoral mobilization, as seen in the 2022 presidential election. Both countries experience increased digital participation alongside heightened polarization and misinformation. The study highlights the need for stronger digital literacy, greater algorithmic transparency, and improved regulation of online political campaigns to protect democratic integrity.